THE USSR OF THE DÉTENTE IN MAFALDA’S ARGENTINA - KRISTINA Buynova (Ибероамериканские тетради)
One of the most successful projects in the history of “serious” comics, Argentinian Mafalda by Quino, was published during the years 1963-1973, when the so-called Argentine Revolution coincided with the détente period. The Cold War and the participation of USSR in it were in Mafalda an important political subject, which became the topic of the present investigation.